Financial Literacy and Financial Technology on Tax Compliance - Sulistiyanti, Umi; Zhafira, Fildzah Tsaltsa; Inayati, Nur Isna; Isthika, Wikan (Studi Akuntansi dan Keuangan Indonesia, 2025)
This study aims to analyze the effect of financial literacy and the use of financial technology on tax compliance moderated by tax digitalization in MSMEs in Yogyakarta. This research uses a quantitative approach. The study was conducted by distributing questionnaires to 120 MSMEs in Yogyakarta. The analysis techniques used in this research are the Multiple Linear Regression Analysis Test and the Moderated Regression Analysis (MRA) Test. The analysis results show that financial literacy and the use of financial technology have a significant positive effect on tax compliance. Meanwhile, tax digitalization is not able to moderate the influence of financial literacy and the use of financial technology on tax compliance.